Throughput Enhancement in TDMA through Carrier Interferometry Pulse Shaping - Natarajan, Bala; Nassar, C.R.; Shattil, S. (Institute of Electrical and Electronics Engineers, 2002)
This paper introduces a novel TDMA scheme that provides enhanced throughput by employing carrier interferometry pulse shapes (CI pulse shapes). At the transmitter, CI pulse shapes are created from the superposition of N carriers, which generates a short mainlobe (pulse) in time. CI pulse shapes are positioned both orthogonally and pseudo-orthogonally in time, enabling the introduction of additional bits into a TDMA burst. Specifically, up to a 100% increase in throughput can be achieved. At the receiver, a novel TDMA detector is deployed where: the pulse shape is broken down into its frequency components and optimally recombined to create frequency diversity benefits. Simulations performed over hilly terrain (HT) and typical urban (TU) GSM channel models indicate that, with a 100% increase in throughput, the proposed system offers up to 6.5 dB performance gains at probability of error of 10-2 relative to a standard GSM system employing a decision feedback receiver
Keywords: Access protocols; Cellular radio; Diversity reception; Error statistics; Fading channels; Feedback